EAPCI Core Curriculum for Percutaneous Cardiovascular Interventions (2020): Committee for Education and Training European Association of Percutaneous Cardiovascular Interventions (EAPCI). A branch of the European Society of Cardiology - Van Belle, Eric; Teles, Rui C; Pyxaras, Stylianos A; Kalpak, Oliver; Johnson, Thomas William; Barbash, Israel Moshe; De Luca, Giuseppe; Kostov, Jorgo; Parma, Radoslaw; Vincent, Flavien; Brugaletta, Salvatore; Debry, Nicolas; et al. (The Official Journal of EuroPCR and the European Association of Percutaneous Cardiovascular Interventions, 2020)
The proposed 2020 Core Curriculum for Percutaneous Cardiovascular Interventions aims to provide an updated European consensus that defines the level of experience and knowledge in the field of Percutaneous Cardiovascular Intervention (PCI). It promotes homogenous education and training programmes among countries, and is the cornerstone of the new EAPCI certification, designed to support the recognition of competencies at the European level and the free movement of certified specialists in the European Community. It is based on a thorough review of the ESC guidelines and of the EAPCI Textbook in Percutaneous Interventional Cardiovascular Medicine. The structure of the current Core Curriculum evolved from previous EAPCI Core Curriuclum and from the "2013 core curriculum of the general cardiologist" to follow the current ESC recommendations for Core Curriculums. In most subject areas, there was a wide - if not unanimous - consensus among the task force members on the training required for the interventional cardiologist of the future. The document recommends that acquisition of competence in Interventional Cardiology requires at least 2 years of postgraduate training, in addition to 4 years devoted to cardiology. The first part of the curriculum covers general aspects of training and is followed by a comprehensive description of the specific components in 54 chapters. Each of the chapters includes statements of the objectives, and is further subdivided into the required knowledge, skills, behaviours, and attitudes.
The proposed 2020 Core Curriculum for Percutaneous Cardiovascular Interventions aims to provide an updated European consensus that defines the level of experience and knowledge in the field of percutaneous cardiovascular intervention (PCI). It promotes homogenous education and training programmes among countries, and is the cornerstone of the new EAPCI certification, designed to support the recognition of competencies at the European level and the free movement of certified specialists in the European Community. It is based on a thorough review of the ESC guidelines and of the EAPCI textbook on percutaneous interventional cardiovascular medicine. The structure of the current core curriculum evolved from previous EAPCI core curricula and from the “2013 core curriculum of the general cardiologist” to follow the current ESC recommendations for core curricula. In most subject areas, there was a wide - if not unanimous - consensus among the task force members on the training required for the interventional cardiologist of the future. The document recommends that acquisition of competence in interventional cardiology requires at least two years of postgraduate training, in addition to four years devoted to cardiology. The first part of the curriculum covers general aspects of training and is followed by a comprehensive description of the specific components in 54 chapters. Each of the chapters includes statements of the objectives, and is further subdivided into the required knowledge, skills, behaviours, and attitudes.
Keywords: Cardiovascular interventions; endovascular